2012
DOI: 10.14419/ijamr.v1i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Application of He’s Method in Solving a System of Nonlinear Coupled Equations Arising in Non-Newtonian Fluid Mechanics

Abstract: In this paper, He's homotopy perturbation method is successfully employed to solve a nonlinear coupled system of ordinary differential equations that arises in the fully developed natural convection flow of a third grade fluid between two vertical parallel walls. The same problem is also solved by a numerical method (Runge-Kutta method of order 4) using the software MAPLE. The numerical results obtained by these methods are then compared and an excellent agreement is observed. This comparative study confirms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is observed that the velocity and temperature distributions decrease with the increase of the non-Newtonian viscous parameter δ, and the highest velocity is manifested in the neighborhood of η = -0.5 in the case at which the non-Newtonian viscous parameter δ is zero In what follows, we investigate the effects of volume fraction φ and the nature of the nanoparticles on the friction and heat transfer coefficients as shown in Figures (10)(11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the velocity and temperature distributions decrease with the increase of the non-Newtonian viscous parameter δ, and the highest velocity is manifested in the neighborhood of η = -0.5 in the case at which the non-Newtonian viscous parameter δ is zero In what follows, we investigate the effects of volume fraction φ and the nature of the nanoparticles on the friction and heat transfer coefficients as shown in Figures (10)(11).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a comparison was made between the numerical and analytical results that were obtained. The work of A.A. Farooq [10] included a thorough comparison between the Runge-Kutta fourth order and the HPM methods; and the study reveals a range of applicability for HPM. Y. Rahmani [11], for his part, considered the presence of nanoparticles (Ag, Cu, 2 3 , and…”
Section: Introductionmentioning
confidence: 99%
“…The natural convection of non-Newtonian fluids has been studied by many authors. [1][2][3][4][5][6][7][8][9][10][11] The natural convection problem between vertical flat plates for a certain class of non-Newtonian fluids has been carried out by Bruce and Na. 1 Rajagopal and Na 2 introduced a numerical solution for natural convection flow of Rivlin-Ericksen fluid and heat transfer between parallel plates.…”
Section: Introductionmentioning
confidence: 99%
“…The method is a useful tool for non-linear problems in science and engineering. Farooq et al 5 presented He's HPM to solve a non-linear coupled system of ordinary differential equations that arises in the fully developed natural convection flow of a third-grade fluid between two vertical parallel walls. The same problem is also solved by a numerical method (Runge-Kutta method of order 4) using the software MAPLE.…”
Section: Introductionmentioning
confidence: 99%